(untitled) (Collection of research papers «PROGRESSIVE TECHNIQUE AND TECHNOLOGIES OF FOOD PRODUCTION ENTERPRISES, CATERING BUSINESS AND TRADE», 2026)
The rise in popularity of the gluten-free diet has led to an increased demand for products made from gluten-free flours such as rice, corn and buckwheat. However, this raw material differs significantly from traditional wheat flour in its protein structure, lack of gluten and specific technological properties, which creates difficulties in ensuring the stable quality of finished products. The study is focused on determining the quality indicators of rice flour, such as moisture, whiteness, protein content and grinding size, to assess its compliance with food industry standards. In order to improve the baking properties of gluten-free dough, during laboratory baking, structuring agents - gelatin and agar - were added. This provided the dough with elasticity and stability, which is necessary to create a uniform texture of the finished bread. Test results showed that the optimal baking mode for such bread is 35 minutes at a temperature of 260 °C. Increasing the duration of baking does not improve the quality of bread, instead it causes an increase in energy consumption, which is not economically justified. Thus, the study proves that rice flour, subject to correction of the recipe with the help of structure formers, is able to ensure high quality of gluten-free bakery products. This opens up prospects for the further use of rice flour in conditions of increased demand for gluten-free products and allows optimizing production processes to achieve stability in the quality of gluten-free bread.